Optimizing Entrepreneurship at the Community Learning Center (CLC) through E-Commerce Marketing - Solfema , Solfema; Wisroni, Wisroni; Sunarti, Vevi; Gusmanti, Reza (Journal of Nonformal Education, 2025)
Community Learning Center (CLC) as one of the government’s partners in educating people’s lives through non-formal education service programs, it is hoped that CLC is not only able to grow a learning society (learning society), but also can improve their abilities and skills in dealing with socio-economic progress through entrepreneurship assistance activities which are one of the focuses of the purpose of the presence of CLC in the midst of the community. The facts on the ground show that CLC, especially in West Sumatra Province, has not been able to optimally become a community education institution that accommodates entrepreneurship-based activities for the community. Entrepreneurial activities carried out by CLC have not been able to create an entrepreneurial spirit and have not been able to maximally facilitate the marketing of CLC business products widely, which is still only local so that CLC entrepreneurial activities are underdeveloped and have not produced significant results. This study aims to see the optimization of entrepreneurship at the Community Learning Activity Center (CLC) through E- Commerce marketing. The results of the study show in fact the main obstacles in the lack of utilization of e-commerce by entrepreneurship activities today are; 1) There is still a lack of understanding of partners regarding E-Commerce; 2) Lack of partner expertise in creating online stores as a means of marketing; 3) Lack of use of smartphones as a marketing medium 4. Lack of partner expertise in operating online stores as a marketing tool